Anxiety in Cancer Patients during 18F-FDG PET/CT Low Dose: A Comparison of Anxiety Levels before and after Imaging Studies - Ana Grilo; Lina Vieira; Elisabete Carolino; Cátia Oliveira; Carolina Pacheco; Maria Castro; Juan Alonso (Nursing Research and Practice)
Objective. Assessing the level of anxiety in oncology patients who underwent 18F-FDG PET/CT low dose scan and identifying the main reasons that generate anxiety. Material and Method. The study included 81 cancer patients submitted to the 18F-FDG PET/CT low dose scan. Patients filled in the Scan Experience Questionnaire and the State-Trait Anxiety Inventory (STAI) before and after 18F-FDG PET/CT low dose scan. Results. Substantial levels of anxiety were detected both before and after 18F-FDG PET/CT low dose scan (STAI mean > 30), with a significant increase in the state of anxiety after scan performance (p<0.0001, Medianpre = 31.1, and Medianpos = 33.0). 18F-FDG PET/CT low dose results are the main cause of anxiety both before (79.1%) and after (86.9%) the scan. The information provided by staff both before and on the 18F-FDG PET/CT low dose day was classified mostly as completely understandable (70.5% and 75.3%, resp.) and as very useful (70.5% and 72.6%, resp.) and correlated positively with patients’ overall satisfaction with NM Department (rS=0.372, p=0.004 and rS=0.528, p = 0.000, resp.), but not with anxiety levels. Conclusions. Patients perceive high levels of anxiety during the 18F-FDG PET/CT low dose scan and the concern with scan results was pointed out as the main factor for that emotional reaction.